(untitled) (Nepalese Journal of Radiology, 2025)
Introduction: Coronavirus Disease-2019 (COVID-19), the global pandemic, caused by Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) infection, was first described in Wuhan city of China in December 2019.1 Diagnosis relies on Reverse Transcriptase polymerase chain reaction (RT- PCR) testing, with high-resolution computed tomography (HRCT) of the chest showing similarities to other viral pneumonias. Post-COVID lung fibrosis can lead to impaired lung function. This study aims to assess pulmonary function in COVID-19 survivors and correlate it with the initial CT severity score on HRCT. Methods: This study was conducted at Dhulikhel Hospital for a duration of one year among 90 patients with moderate to severe COVID-19 pneumonia. HRCT chest was performed during admission and was categorized using the CT severity score. Spirometry tests were conducted after three months and were compared with the initial HRCT findings. Results: Among 90 patients, 42(46.7%) were females and 48(53.3 %) were males. The most common spirometry findings in post-COVID-19 patients were a restrictive pattern. Statistically significant correlation was observed between the spirometry findings and initial HRCT findings, suggesting that with increasing degree of CT severity, there was decreased respiratory function during follow-up. Age had a significant correlation with spirometry findings. No association of gender with CT severity score and spirometry was seen in our study. Conclusions: The result of this study showed that increasing CT severity score could later lead to impairment in pulmonary function. Restrictive lung disease is the predominant lung function impairment in post-COVID-19 pneumonia cases.